PROSESI RITUAL ADAT NGAMALO SUKU DAYAK KANAYATN DESA KELAMPAI SETOLO KABUPATEN LANDAK KALIMANTAN BARA - Sutronan, Friskatry (Universitas Tanjungpura, 2024)
The Ngamalo Traditional Ritual is a hereditary practice conducted by the Dayak Kanayatn community as a prelude to planting rice seeds. It is vital to make suitable preparations in order to effectively perform the Ngamalo ceremony. Gathering the necessary tools and ingredients includes gathering kalangkakng, a pair of native hens (one female and one male), chicken eggs, poe cooked in bamboo, bontok'ng, palame, tumpi, and a machete. The current research problem is...